The Role of Sharia Economic Law in Poverty Alleviation Efforts - Nikita Majdina; Dio Sandri Wijaya; Yufitri Ezwandi (Saqifah: Jurnal Hukum Ekonomi Syariah, 2024)
This article explores the role of Sharia economic law in poverty alleviation efforts using a literature review type of research. Data sources were obtained by searching for references from literature reviews that were relevant to the cases or problems found. Data was obtained through searches on Google Scholar, books and research-related scientific works. The results of this research are that Islamic Economic Law is regulations relating to economic practices in the fields of production, distribution and consumption based on Islamic law sourced from the Al-Qur'an and As-Sunnah as well as the consensus of the ulama with the aim of realizing prosperity and benefit for all mankind both in this world and in the afterlife. Islamic economics or Sharia economics has a very crucial role in efforts to eradicate poverty, namely realizing justice and economic balance, improving community welfare, encouraging community economic empowerment